Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.14814/phy2.14800
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 and hypertension

Abstract: The objective of this review is to give an overview of the pathophysiological effects of the Coronavirus Disease 2019 (COVID‐19) in relation to hypertension (HT), with a focus on the Renin–Angiotensin–Aldosterone System (RAAS) and the MAS receptor. HT is a multifactorial disease and a public health burden, as it is a risk factor for diseases like stroke, coronary artery disease, and heart failure, leading to 10.4 million deaths yearly. Blood pressure is regulated by the RAAS. The system consists of two counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 106 publications
1
14
0
3
Order By: Relevance
“…Hypertension, like other cardiovascular diseases, has been associated with increased mortality in patients hospitalized for COVID-19 [ 4 , 14 , 15 ]. In our study, it was the most frequent comorbidity in the NS group (34.46%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, like other cardiovascular diseases, has been associated with increased mortality in patients hospitalized for COVID-19 [ 4 , 14 , 15 ]. In our study, it was the most frequent comorbidity in the NS group (34.46%).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent meta-analysis published by Chang Chu et al concluded that angiotensin-converting enzyme inhibitors (ACEIs) reduce the risk of SARS-CoV-2 infection and all causes of COVID-19 mortality, including the risk of non-COVID-19 pneumonia [ 16 ]. The exact mechanism of hypertension related to the COVID-19 severity remains unclear [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dengan demikian, konsekuensi ACE/AngII/AT1R dapat dikurangi dengan mengaktifkan jalur ACE2/Ang1-7/MasR. 18,20 Ekspresi ACE2 secara substansial meningkat pada pasien dengan hipertensi, yang diobati dengan inhibitor RAAS, seperti ACEI dan ARB. Karena ACE2 memfasilitasi masuknya SARS-CoV-2 ke dalam sel target, terdapat hipotesis bahwa penggunaan inhibitor RAAS yang sudah ada sebelumnya dapat meningkatkan risiko menderita COVID-19, dan mengonsumsinya selama infeksi dapat memperburuk hasil klinis.…”
Section: Bahasanunclassified
“…Karena ACE2 memfasilitasi masuknya SARS-CoV-2 ke dalam sel target, terdapat hipotesis bahwa penggunaan inhibitor RAAS yang sudah ada sebelumnya dapat meningkatkan risiko menderita COVID-19, dan mengonsumsinya selama infeksi dapat memperburuk hasil klinis. 21,20 Namun studi yang dilakukan Chen et al 8 mengungkapkan bahwa pasien yang menerima inhibitor RAAS sebelum masuk memiliki tingkat yang lebih rendah untuk hasil klinis yang merugikan. Pasien hipertensi yang menerima inhibitor RAAS, baik sebelum atau setelah masuk, memiliki penurunan risiko perkembangan hasil klinis yang merugikan, termasuk kematian, acute respiratory distress syndrome (ARDS), gagal napas, syok septik, ventilasi mekanis, dan masuk ICU.…”
Section: Bahasanunclassified
See 1 more Smart Citation